2017
DOI: 10.33373/anglo.v8i1.980
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Whispering Game to Students’ Vocabulary Mastery

Abstract: In this research, there are many problems in learning process in the class. The problems are lack of vocabulary, and method of teaching vocabulary used. This research has purpose to students’ vocabulary mastery by using whispering game at the SMP Kartini II Batam academic Year 2015/2016. This research is quantitative research. The researcher used total sampling. The experimental class was taught using whispering game, whereas the control class was taught using lecturing method. In this research, the researcher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is supported by the statement of Sinaga et al (2020), which states that many EFL teachers have difficulty teaching. One of the causes of this problem is the lack of vocabulary, which causes EFL learners to find it challenging to memorize vocabulary and lazy to learn (Sihaloho et al, 2017). Another reason is that EFL learners are less motivated to learn EFL, so the vocabulary mastered is only a little (Altun & Khdhir, 2022;Iaremenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the statement of Sinaga et al (2020), which states that many EFL teachers have difficulty teaching. One of the causes of this problem is the lack of vocabulary, which causes EFL learners to find it challenging to memorize vocabulary and lazy to learn (Sihaloho et al, 2017). Another reason is that EFL learners are less motivated to learn EFL, so the vocabulary mastered is only a little (Altun & Khdhir, 2022;Iaremenko, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reports that students often find it challenging to understand and learn English because students lack the motivation to learn English (Iaremenko, 2017;Sihaloho et al, 2017). Students also often find it difficult when to speak and read English.…”
Section: Introductionmentioning
confidence: 99%
“…And the result of the research showed that Whispering Game is effective used to improve students' listening skill. The result of analysis can be concluded that the use of whispering game at Second semester UNRIKA in academic year 2016/2017 gave significant effect in the students' activity in learning process than the use of old technique [5].…”
Section: Introductionmentioning
confidence: 96%